2021
DOI: 10.3171/2021.3.focus201044
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced biomaterials: systematic review of alternatives to supplement spine fusion including silicon nitride, bioactive glass, amino peptide bone graft, and tantalum

Abstract: OBJECTIVE Spinal fusions are among the most common and effective spinal surgical practices; however, the current model presents some cost and safety concerns within the patient population. Therefore, enhanced biomaterials have been presented to be an innovative yet underutilized tool to supplement the success of spinal fusion surgery. Herein, the authors discuss these biomaterials, their compositions, clinical outcomes, and cost analysis through a systematic review of the literature to date. METHODS This sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 58 publications
(70 reference statements)
1
14
0
Order By: Relevance
“…Increased surface roughness reportedly promoted osteoblast spread and migration ( Jiang et al, 2013 ; Abar et al, 2021 ). In the cell viability tests, as an inorganic nanomaterial with excellent biocompatibility, Si 3 N 4 did not show significant cytotoxicity, consistent with previous reports ( Bock et al, 2015 ; Fiani et al, 2021 ; Lee et al, 2021 ). Regarding osteogenic differentiation, Si 3 N 4 doping significantly promoted ALP and mineralization compared to the control group, possibly due to the slight dissolution of Si 3 N 4 in the body fluid environment and the slow release of Si 4+ .…”
Section: Resultssupporting
confidence: 91%
“…Increased surface roughness reportedly promoted osteoblast spread and migration ( Jiang et al, 2013 ; Abar et al, 2021 ). In the cell viability tests, as an inorganic nanomaterial with excellent biocompatibility, Si 3 N 4 did not show significant cytotoxicity, consistent with previous reports ( Bock et al, 2015 ; Fiani et al, 2021 ; Lee et al, 2021 ). Regarding osteogenic differentiation, Si 3 N 4 doping significantly promoted ALP and mineralization compared to the control group, possibly due to the slight dissolution of Si 3 N 4 in the body fluid environment and the slow release of Si 4+ .…”
Section: Resultssupporting
confidence: 91%
“…Recently, Fiani et al, 2021, found that Si 3 N 4 and other biomaterials can act as suitable fusion expanders given their favorable properties. [38] Significant limitations must be considered while assessing the generalizability of the results. The literature is inconsistent in its definitions of subsidence and the lack of randomized control trials remains pervasive.…”
Section: Discussionmentioning
confidence: 99%
“…The sparse data that does exist suggests that silicon nitride may afford earlier fusions and less infections from inherent bacteriostatic properties. [5] , [6] , [7] However, contradictory data also exists (i.e., SNAP trial [8] ) that alludes to the fact that Si 3 N 4 may not be superior or even comparable to PEEK, whereas another RCT by McEntire BJ et al. [9] , demonstrated non-inferiority to PEEK.…”
Section: Introductionmentioning
confidence: 99%
“…1 A promising approach is the functionalization of bone implants with bone growth-stimulating agents, such as silicon or strontium ions. [2][3][4][5][6][7][8][9][10][11] This applies in particular in the case of osteoporosis patients, who suffer from delayed fracture healing. 12 Sr 2+ has proven to be an effective therapeutic agent in the treatment of osteoporosis, mainly because of the double positive effect of Sr 2+ ions on bone metabolism: They are able to inhibit osteoclastic bone resorption and simultaneously promote new bone formation by stimulating bone-building osteoblasts.…”
Section: Introductionmentioning
confidence: 99%
“…Next‐generation biomaterials for bone fractures will be functionalized with drug release systems as well as antibiotic agents 1 . A promising approach is the functionalization of bone implants with bone growth‐stimulating agents, such as silicon or strontium ions 2–11 . This applies in particular in the case of osteoporosis patients, who suffer from delayed fracture healing 12 .…”
Section: Introductionmentioning
confidence: 99%